Extended duration dual antiplatelet therapy and mortality: a systematic review and meta-analysis. Issue 9970 (28th February 2015) - Elmariah, Sammy; Mauri, Laura; Doros, Gheorghe; Galper, Benjamin Z; O'Neill, Kelly E; Steg, Philippe Gabriel; Kereiakes, Dean J; Yeh, Robert W
Summary: Background: Treatment with aspirin and a P2Y12 inhibitor is commonly used in patients with cardiovascular disorders. The overall effect of such treatment on all-cause mortality is unknown. In the Dual Antiplatelet Therapy (DAPT) Study, continuation of dual antiplatelet therapy beyond 12 months after coronary stenting was associated with an unexpected increase in non-cardiovascular death. In view of the potential public health importance of these findings, we aimed to assess the effect of extended duration dual antiplatelet therapy on mortality by doing a meta-analysis of all randomised, controlled trials of treatment duration in various cardiovascular disorders. Methods: We searched Medline, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) to identify randomised controlled trials assessing the effect of extended duration versus no or short duration dual antiplatelet therapy, published before Oct 1, 2014. We did a meta-analysis to pool results with a hierarchical Bayesian random-effects model. The primary outcomes were hazard ratios comparing rates of all-cause, cardiovascular, and non-cardiovascular death. Findings: Including the DAPT Study, we identified 14 eligible trials that randomly assigned 69 644 participants to different durations of dual antiplatelet therapy. Compared with aspirin alone or short duration dual antiplatelet therapy (≤6 months), continued treatment was not associated with a difference in all-cause mortality (hazard ratio [HR] 1·05, 95% credible interval [CrI] 0·96–1·19; p=0·33). Similarly, cardiovascular (1·01, 0·93–1·12; p=0·81) and non-cardiovascular mortality (1·04, 0·90–1·26; p=0·66) were no different with extended duration versus short duration dual antiplatelet therapy or aspirin alone. Interpretation: Extended duration dual antiplatelet therapy was not associated with a difference in the risk of all-cause, cardiovascular, or non-cardiovascular death compared with aspirin alone or short duration dual antiplatelet therapy. Funding: None.